Anticancer Activities of Tumor-killing Nanorobots. Issue 6 (June 2019) - Li, Suping; Jiang, Qiao; Ding, Baoquan; Nie, Guangjun
Abstract : Pharmaceutical uses of cancer therapeutics, such as intravenous thrombin to elicit blood coagulation, have been hampered by lack of tumor specificity. Based on rapid progress in DNA origami-based machines capable of transporting molecular payloads, DNA nanorobots have been constructed to specifically deliver therapeutic agents into tumor vessels.